Data-Driven Stakeholder Management in EU Capacity Building Projects – Case of Erasmus+ Project - Radoslav BARISIC; Dominik VUKUSIC (Communications of International Proceedings, 2023)
Data-driven management of stakeholders could be one of very important factors of successful project administration, particularly with regards to strategies involving different players such as those engaged in EU capacity building initiatives like Erasmus+. Effective stakeholder management entails identifying and overseeing various stakeholder groups to meet their needs and expectations, which is of a great importance for final success of the project. Therefore, we decided to aim our analysis in understanding stakeholder background which is of a vital importance as various characteristics may reveal differences in preferences; for instance, location preferences could impact engagement strategies and communication methods with them. Long-term project success depends on a project manager implementing tasks to study stakeholder information, goals, and characteristics to meet future project goals. Effective stakeholder management is also important for projects that aim to strengthen organizations' abilities to face their own challenges and meet the development goals, especially those located in transitional countries. To ensure project success, imperative is that project managers tailor stakeholder management approaches according to individual expectations and interests. Engagement strategies must consider stakeholder preferences as well as budget limitations for effective communication and participation which will lead to overall better efficiency and achievement of project goals and general impact.
Keywords: stakeholders; development; strategy; and data analytics